Automated system of the technological process for the production of ceramic bricks. - Kairedenov Асыланбек (Рroblems of engineering and professional education, 2023)
Wardrobe mimic automation, microprocessor controller to implement control functions at a low level and the workstation.Improved automation of ceramic bricks production process through the development of discrete models of functioning technological units.The procedure for the synthesis of discrete systems of automation of technological processes of production of ceramic bricks in the class distributed control and computing systems have the property of resiliency and survivability based on the concept of disaggregated process.